Collagen breaks at weak sacrificial bonds taming its mechanoradicals [data] - Rennekamp, Benedikt; Gräter, Frauke (Universität, 2023)
This dataset contains input files for MD simulations, derived breakage counts from these simulations that are used to generate the figures in the p...
Gesehen am 27.03.2023
Keywords: Forschungsdaten; Datenbank